2021
DOI: 10.4102/hts.v77i4.6341
|View full text |Cite
|
Sign up to set email alerts
|

Transversal modes of being a missional church in the digital context of COVID-19

Abstract: The disruptions of coronavirus disease 2019 (COVID-19) in the year 2020 reshaped all aspects of life, including religious practices and rituals. As more religious activities shifted to digital space during the lockdown periods, there was a growing need to examine the link between religion and digital media. Using the model of the Uniting Presbyterian Church in Southern Africa (UPCSA), this article draws on the notion of transversal rationality and concepts of rationality, cognitive, evaluative and pragmatic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In his "Transversal modes of being a missional church in the digital context of COVID-19," the missiologist Buhle Mpofu examines the link between religion and digital media from the vantage point that COVID-19 configured traditional missional and liturgical spaces in ways that locate the agency of the marginalized at the center. 27 30 He rightly and insightfully argues that COVID-19 has brought about very complex challenges to such extent that it can only be carried on through interdisciplinary approaches. As interdisciplinary conversation partners he engages and negotiates as theologian with the fields of virology and philosophy of biology.…”
Section: Some Reactionsmentioning
confidence: 99%
“…In his "Transversal modes of being a missional church in the digital context of COVID-19," the missiologist Buhle Mpofu examines the link between religion and digital media from the vantage point that COVID-19 configured traditional missional and liturgical spaces in ways that locate the agency of the marginalized at the center. 27 30 He rightly and insightfully argues that COVID-19 has brought about very complex challenges to such extent that it can only be carried on through interdisciplinary approaches. As interdisciplinary conversation partners he engages and negotiates as theologian with the fields of virology and philosophy of biology.…”
Section: Some Reactionsmentioning
confidence: 99%
“…The COVID-19 disruptions presented an opportunity to interrogate traditional practices related to dispensing of the Holy Communion within the Reformed tradition and explore other missional alternatives. Mpofu (2021) also observed that the creative use digital connections and spaces demonstrate how transnational faith communities create digital liturgical spaces across borders that redefined 'presence' and the 'none present' in ways that could enhance mission in the era of social distancing necessitated by responses to COVID-19:…”
Section: Introductionmentioning
confidence: 99%